PENGARUH INVESTMENT OPPORTUNITY SET (IOS) TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAGEMENT OWNERSHIP SEBAGAI VARIABEL MODERASI (STUDI KASUS PADA PERUSAHAAN SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI) - Erna Hayati; Fitri Nurjanah; Violyvya Ardiantika Putri (JURNAL ILMIAH EDUNOMIKA, 2022)
The company's financial performance is a measure that can show the extent to which a company has achieved success. Investment Opportunity Set (IOS) is one of the factors that determine financial performance. Management ownership as one of the factors in good corporate governance that can strengthen or weaken the relationship between IOS and the company's financial performance. So the purpose of the proposed research is to prove whether the Investment Opportunity Set has an effect on financial performance with a moderating effect of management ownership. Food and beverage sector companies are used as case studies in this study. The food and beverage sector is one sector that is considered to still be able to survive in the midst of the economic crisis due to the Covid-19 pandemic. The data used is the annual report of the food and beverage sector companies from 2015 to 2020. The method in analyzing the data in this study uses the Moderated Regression Analysis (MRA) method. The results of hypothesis testing indicate that IOS partially has a significant effect on improving the financial performance of manufacturing companies on the Indonesia Stock Exchange in the food and beverage sector. While the very small percentage of Management ownership causes this variable to have no significant effect either partially or as a moderating variable.